2012
DOI: 10.1111/j.1365-2214.2012.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Korean version of the manual ability classification system for children with cerebral palsy

Abstract: The Korean version of the MACS is reliable and valid and is suitable for assessing manual ability in Korean children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 6 publications
2
17
0
2
Order By: Relevance
“…The validity and reliability of MACS classification has been well-established, and ranges from level I (the child handles most objects), to level V (the child cannot handle any object) for children aged 4 to 18 years [9]. Korean versions of PEDI and MACS are widely used, both of which have also been shown to be valid and reliable [1011]. …”
Section: Methodsmentioning
confidence: 99%
“…The validity and reliability of MACS classification has been well-established, and ranges from level I (the child handles most objects), to level V (the child cannot handle any object) for children aged 4 to 18 years [9]. Korean versions of PEDI and MACS are widely used, both of which have also been shown to be valid and reliable [1011]. …”
Section: Methodsmentioning
confidence: 99%
“…In several studies, the inter-and intrarater reliability of the MACS has been found to be good to excellent between therapists as well as between parents and therapists, varying from 0.73 to 0.98 and 0.91 to 0.98 respectively. 2,[4][5][6][7][8][9][10][11] There is also evidence supporting the stability of MACS classifications over a short period. In a previous study, the intraclass correlation coefficient (ICC) was high (0.92) and 67% of the children remained at the same level over a period of 1 year when scored by caregivers.…”
mentioning
confidence: 93%
“…Besides, health professional vs. patient self-evaluation data were collected in order to compare results of QUIP-RS Brazil from health professional and patients self-evaluation. 17 There was a time difference from 20 min to 30 min between both measurements (firstly professional and subsequently patient self-evaluation). Both measurements were performed during the morning.…”
Section: Measurement Propertiesmentioning
confidence: 99%